PERAN ORANG TUA DALAM MENDUKUNG PRESTASI OLAHRAGA SEPAK BOLA PUTRI DI LAMONGAN - Sherif Juniar Aryanto; Muhammad Wahyono; Pratiwi Viyanti; Ramadhani Hananto Puriana; Achmad Nuryadi; Bayu Akbar Harmono (STAND, 2023)
Parents are the first people who influence the growth and development of children, so that the important role of parents is to analyze, support, direct and develop the potential of their children, so that it is the support from parents that encourages children's achievements. This study aims to find out how much support the athletes have for the sports achievements of women's football in Lamongan. There are three factors that support children's sports achievements, namely 1) Attention; 2) Facilities in the form of infrastructure and nutritional intake; 3) Social support from the surrounding environment. Based on the results obtained, 53% were categorized as good and 30% were categorized as sufficient so that the parents of the athletes were good at supporting Lamongan women's football sports achievements, but 17% were categorized as very lacking. parents in fulfilling good nutritional intake for Lamongan women's football athletes, even so the average result obtained was 91, which means that the role of parents in supporting Lamongan women's football sports achievements is categorized as sufficient.